CORRUPTION IN THE LAND SECTOR - Papic Brankov, Tatjana; Tanjević, Nataša (Economics of Agriculture, 2013)
The corruption is both a major cause and a result of poverty around the world. Corruption in the land sector can be generally characterized as pervasive and without effective means of control. In this paper we analyze the risks and forms of corruption in the land sector citing some documented examples from the world and from Serbia. The paper concludes that all countries facing a problems with land administration needs the rebuilding of land administration institutions to provide access to land as essential to rekindle economic growth and social stability. It can also be concluded that Serbia is on the path of mild progress in planning land administration and land management.